The Mediating Role of Brand Love between Brand Personality and Brand Loyalty: A Study on SMEs Traditional Woven Fabric in Indonesia (Journal of Entrepreneurship and Business, 2024)
This paper aimed to examine the impact of brand personality dimensions (sincerity, excitement, and competence) on brand loyalty. In addition, the role of brand love is explored through mediation models. A total of 384 valid and usable responses collected from a consumer of Traditional SME Traditional Woven fabric in Indonesia were analyzed through the structural equation model (SEM). A research model examined several hypotheses underpinned by multidimensional brand loyalty and interpersonal love. The findings showed that sincerity and competence had a significant impact on brand loyalty and brand love, but excitement had no significant impact on brand loyalty and brand love. Moreover, brand love mediated the relationship between sincerity and competence, but excitement had an insignificant impact. The results of this study indicate that small and medium-sized enterprises (SMEs) in the traditional woven fabric industry should foster emotions to establish a robust consumer-brand connection. Furthermore, it is critical to prioritize the development of robust attributes, as traditional woven textiles possess deeply ingrained cultural significance. This study contributes to the current knowledge of brand loyalty literature by exploring the characteristics of brand personality and brand love. The findings imply that when consumers' brand personality is mixed with brand love, it will result in increased loyalty towards the brand.
Keywords: Array; Array; Array; Array; Array; Array